Stromal Cell-Derived Factor (SDF) 2 and the Endoplasmic Reticulum Stress Response of Trophoblast Cells in Gestational Diabetes Mellitus and In vitro Hyperglycaemic Condition - Lorenzon, Aline R.; Moreli, Jusciele B.; de Macedo Melo, Rafaela; Namba, Felipe Yukio; Staff, Anne Cathrine; Yung, Hong Wa; Burton, Graham J.; Bevilacqua, Estela (Current Vascular Pharmacology, 2021)
Background and Aim: The endoplasmic reticulum (ER) stress response and the unfolded protein response (UPR) are essential cellular mechanisms to ensure the proper functioning of ER in adverse conditions. However, activation of these pathways has also been associated with insulin resistance and cell death in pathological conditions such as diabetes mellitus. In the present study, we investigated whether stromal cell-derived factor 2 (SDF2)—an ER stress-responsive factor—is related to ER response in placental cells exposed to maternal gestational diabetes mellitus (GDM) or to a hyperglycaemic in vitro condition. Objective: The study aimed to investigate the role of SDF2 in BeWo cells , a trophoblast cell line originating from choriocarcinoma , and in placental tissue under hyperglycaemic conditions. Methods: Protein levels of SDF2 and UPR factors, glucose-related protein 78 (GRP78) and eukaryotic initiation factor 2 alpha (elF2 alpha) were evaluated in the placentae of pregnant women diagnosed with GDM and treated by diet-control (insulin was added when necessary). The mRNA expression of SDF2 and UPR factors CHOP and sXBP1 were assessed in cultured BeWo cells challenged with glucose and treated with or without insulin. Results: SDF2 expression was increased in the placentae of GDM women treated with diet. However, its values were similar to those of normoglycemic controls when the GDM women were treated with insulin and diet. BeWo cells cultured with high glucose and insulin showed decreased SDF2 expression, while high glucose increased CHOP and sXBP1 expression, which was then significantly reverted with insulin treatment. Conclusion: Our findings extend the understanding of ER stress and SDF2 expression in placentae exposed to hyperglycaemia, highlighting the relevance of insulin in reducing the levels of ER stress factors in placental cells. Understanding the effect of ER stress partners such as SDF2 on signalling pathways involved in gestation, complicated by hyperglycaemia, is pivotal for basic biomedical research and may lead to new therapeutic possibilities.
Keywords: gestational diabetes mellitus